2021
DOI: 10.1016/j.bbrep.2021.101054
|View full text |Cite
|
Sign up to set email alerts
|

CFTR-mediated anion secretion in parathyroid hormone-treated Caco-2 cells is associated with PKA and PI3K phosphorylation but not intracellular pH changes or Na+/K+-ATPase abundance

Abstract: Parathyroid hormone (PTH) has previously been shown to enhance the transepithelial secretion of Cl − and HCO 3 − across the intestinal epithelia including Caco-2 monolayer, but the underlying cellular mechanisms are not completely understood. Herein, we identified the major signaling pathways that possibly mediated the PTH action to its known target anion channel, i.e., cystic fibrosis transmembrane conductance regulator anion channel (CFTR). Specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The results were validated via the commercially available fluorometric assay based on the cell-permeable fluorescent indicator BCFL-AM. 58 , 59 In all the cases using the pH nanosensor, six different cells were analyzed to obtain average pH values with their corresponding deviations ( n = 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results were validated via the commercially available fluorometric assay based on the cell-permeable fluorescent indicator BCFL-AM. 58 , 59 In all the cases using the pH nanosensor, six different cells were analyzed to obtain average pH values with their corresponding deviations ( n = 6).…”
Section: Resultsmentioning
confidence: 99%
“…As a control experiment, the pH i of a single PC12 cell was traced during the same time frame and without the addition of cariporide. The results were validated via the commercially available fluorometric assay based on the cell-permeable fluorescent indicator BCFL-AM. , In all the cases using the pH nanosensor, six different cells were analyzed to obtain average pH values with their corresponding deviations ( n = 6).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the exact mechanism of CFTR action as a crucial player in calcium transport remains elusive. We previously reported that the salient calcium-regulating hormone PTH could directly stimulate CFTR opening, thereby enhancing HCO 3 transport across Caco-2 monolayer [7,37], while incubating Caco-2 monolayer in HCO 3 --free solution markedly diminished PTH-induced anion transport [38]. Thus, Caco-2 cells used CFTR to transport HCO 3 -, which might, in turn, affect calcium transport.…”
Section: Plos Onementioning
confidence: 99%